2018
DOI: 10.1007/s00405-018-5055-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro detection of common rhinosinusitis bacteria by the eNose utilising differential mobility spectrometry

Abstract: Acute rhinosinusitis (ARS) is a sudden, symptomatic inflammation of the nasal and paranasal mucosa. It is usually caused by respiratory virus infection, but bacteria complicate for a small number of ARS patients. The differential diagnostics between viral and bacterial pathogens is difficult and currently no rapid methodology exists, so antibiotics are overprescribed. The electronic nose (eNose) has shown the ability to detect diseases from gas mixtures. Differential mobility spectrometry (DMS) is a next-gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In recent years, with the rapid development of machine learning, the combination of electronic noses and pattern recognition models such as KNN, RF, SVM, CNN, and BPNN in machine learning has increased the prominence of the electronic nose in many fields. Virtanen et al successfully identified five common pathogenic bacteria of acute sinusitis by combining the electronic nose and KNN while providing a pathological basis for the treatment of acute sinusitis [ 16 ]. Tian et al made full use of the advantages of high RF stability, short time consumption, and high precision, and proposed an electronic nose and RF model based on the rapid detection of yogurt flavor acceptability.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, with the rapid development of machine learning, the combination of electronic noses and pattern recognition models such as KNN, RF, SVM, CNN, and BPNN in machine learning has increased the prominence of the electronic nose in many fields. Virtanen et al successfully identified five common pathogenic bacteria of acute sinusitis by combining the electronic nose and KNN while providing a pathological basis for the treatment of acute sinusitis [ 16 ]. Tian et al made full use of the advantages of high RF stability, short time consumption, and high precision, and proposed an electronic nose and RF model based on the rapid detection of yogurt flavor acceptability.…”
Section: Methodsmentioning
confidence: 99%
“…The gas sensor circuit converts odor into a voltage signal, and the STM32F334 microprocessor performs ADC (analog-to-digital conversion). The acquisition process simulates human breathing action [ 11 ]. The acquisition process once is divided into the following steps: 500 ms DC motor reverses; at this time, the wind blows out from the wind drum to achieve ‘exhalation’; 2000 ms DC motor is forward; at this time, the wind is sucked into the air cylinder from outside to realize ‘suction’; 500 ms DC motor reverses; at this time, the wind blows out from the wind drum, to achieve ‘exhalation’.…”
Section: Hardware Design Of Electric Nosementioning
confidence: 99%
“…9 Moreover, an in vitro study revealed that DMS was able to discriminate the 4 most common reported ARS bacteria with an accuracy of 85%. 10 Although the results are encouraging, they might be drastically different when samples are acquired ex vivo, as inflammatory response to infection and exogenous VOCs can interfere with the analysis of VOCs. 11 The aim of this pilot study was to examine patients with ARS symptoms and to determine whether maxillary sinus secretions demonstrate different VOC profiles in DMS analysis when bacteria are present.…”
Section: Introductionmentioning
confidence: 99%